The ICARE Learning Model: Transforming Islamic Religious Education Learning Outcomes - Shabina Intan Wardani; Heru juabdin Sada; Waluyo Erry Wahyudi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The main background of this research is the low analytical ability of students (cognitive level C4) in Islamic Religious Education at Junior High School 1 Jati Agung. Lack of activity, low learning independence, and the prevalence of conventional learning methods with minimal innovation trigger this phenomenon. This study aims to analyze the effectiveness of the ICARE (Introduction, Connection, Application, Reflection, Extension) learning model as a transformative strategy in significantly improving student learning outcomes. This study uses a quantitative approach with a post-test-only control group design. The research sample was determined through a simple random sampling technique, which was divided into a control class (VII A) and an experimental class (VII B). Data was collected through a multiple-choice test instrument specifically designed to measure the analysis indicator (C4). Data analysis techniques include normality tests, homogeneity tests, and t-tests to verify differences in average learning outcomes between groups. The research findings indicate that the implementation of the ICARE model has a significant impact on the transformation of student learning outcomes. This result is proven through statistical tests with a significant value of 0.001 (p < 0.05). ICARE syntax organizes real-life experiences with concept understanding, encouraging students to participate and think critically. This study offers Islamic Religious Education (PAI) educators’ new ways to create a dynamic and immersive learning environment. ICARE has been successful in transitioning from passive to outcome-oriented learning and accelerated cognitive development.